Bonding analysis of water clusters using quasi-atomic orbitals. Issue 34 (19th August 2021) - Galvez Vallejo, Jorge L.; Heredia, Juan Duchimaza; Gordon, Mark S.
Abstract : The quasi-atomic orbital (QUAO) bonding analysis introduced by Ruedenberg et al. is used to develop an understanding of the hydrogen bonds in small water clusters, from the dimer to the hexamer (bag, boat, book, cyclic, prism and cage conformers). Abstract : The quasi-atomic orbital (QUAO) bonding analysis introduced by Ruedenberg and co-workers is used to develop an understanding of the hydrogen bonds in small water clusters, from the dimer through the hexamer (bag, boat, book, cyclic, prism and cage conformers). Using kinetic bond orders as a metric, it is demonstrated that as the number of waters in simple cyclic clusters increases, the hydrogen bonds strengthen, from the dimer through the cyclic hexamer. However, for the more complex hexamer isomers, the strength of the hydrogen bonds varies, depending on whether the cluster contains double acceptors and/or double donors. The QUAO analysis also reveals the three-center bonding nature of hydrogen bonds in water clusters.